The Effect of Contextual Teaching and Learning Models on Al-Quran and Hadith Subjects - Sabarudin, Mohammad; Al Ayyubi, Ibnu Imam; Rohmatulloh, Rifqi; Indriyani, Siti (At-tadzkir: Islamic Education Journal, 2023)
This research was conducted at MTs Arrukhshatul 'Ulum West Bandung with quantitative research using survey methods with correlation analysis to see the relationship between student learning independence and student learning outcomes using the Contextual Teaching and Learning (CTL) learning model on Al-Qur'an and Hadith material. The population of this study was class VII students at MTs Arrukhshatul 'Ulum with a sample of 32 students. From the research conducted, it was found that the independent variable and the dependent variable had a very low correlation with a Correlation Coefficient value of 0.064 because it was found in the interval 0.00-0.19 and the significance value of the Correlation was 0.729 which means there was no correlation between student learning independence and learning outcomes students use the Contextual Teaching and Learning (CTL) learning model on Al-Qur'an and Hadith material. This study did not carry out a linear regression test because the data were not normally distributed.